Development of the internal reproductive organs in early nymphal stages of Archegozetes longisetosus Aoki (Acari, Oribatida, Trhypochthoniidae) as obtained by synchrotron X-ray microtomography (SR-μCT) and transmission electron microscopy (TEM) - Paavo Bergmann; Michael Heethoff (Soil Organisms, 2012)
We studied the development of the internal reproductive organs in juvenile stages of Archegozetes longisetosus. 3D-renderings of organs were obtained from synchrotron X-ray microtomography (SR- µCT). In addition, transmission electron microscopy (TEM) was used to obtain cytological details. The reproductive organs develop from an unpaired, ventral mass of mesodermal tissue in the larva, and development progresses continuously and largely independent from the development of other organs or moltings. Volume increase of the ovary and a growing number of germ cells indicate proliferation of oogonia in the deutonymph. The oviducts develop from dorso-lateral extensions of mesodermal somatic tissue.